2009
DOI: 10.1007/s12275-008-0206-z
|View full text |Cite
|
Sign up to set email alerts
|

Class 1 and class 2 integrons and plasmid-mediated antibiotic resistance in coliforms isolated from ten rivers in northern Turkey

Abstract: We aimed to determine the molecular mechanisms of antibiotic resistance in coliforms isolated from ten rivers in northern region of Turkey. A total of 183 isolates were tested for antimicrobial susceptibility by disk diffusion and agar dilution methods. Resistance to ampicillin, streptomycin, trimethoprim, tetracycline, and chloramphenicol was detected in 58%, 51.9%, 24%, 28.4%, and 12.5%, respectively. Twelve (6.5%) phylogenetically distant organisms were detected to harbor self-transmissible plasmids ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
2
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 40 publications
4
37
2
5
Order By: Relevance
“…In another study conducted on 322 E. coli strains previously isolated from irrigation water and associated sediments at the El Paso, Presidio, and Weslaco regions of the river, only one isolate was detected to contain class 2 integron (Matthew, 2003). In an investigation on antibiotic resistance mechanism in 183 coliforms isolated from ten rivers in northern region of Turkey, 2.7% (5/183) of the coliforms harbored class 1 and class 2 integrons, respectively (Ozgumus et al, 2009). As K. pneumoniae was concerned, the occurrence was low.…”
Section: Class 2 Integronmentioning
confidence: 99%
“…In another study conducted on 322 E. coli strains previously isolated from irrigation water and associated sediments at the El Paso, Presidio, and Weslaco regions of the river, only one isolate was detected to contain class 2 integron (Matthew, 2003). In an investigation on antibiotic resistance mechanism in 183 coliforms isolated from ten rivers in northern region of Turkey, 2.7% (5/183) of the coliforms harbored class 1 and class 2 integrons, respectively (Ozgumus et al, 2009). As K. pneumoniae was concerned, the occurrence was low.…”
Section: Class 2 Integronmentioning
confidence: 99%
“…Ozgumus et al, examined seawater based coliforms class 1 and class 2 integron gene tapes and antibiotic resistance characteristics. The study found that ampicillin resistant E.coli contained the TEM-1 type β-lactamase gene 20 . Also, they found that among the tetracycline resistant strains, the tet (B) gene was common.…”
Section: Discussionmentioning
confidence: 98%
“…Ampisiline karşı yüksek bir (% 81,73) direnç tespit edilmiş ve seftazidim de direnç oranı olarak (% 13,5) ikinci sırada yer almıştır. Yapı-lan birçok çalışma klinikte oldukça sıklıkla kullanılan beta-laktam antibiyotiklerine karşı yüksek oranda direncin birçok çevreden izole edilen enterik bakterilerde bulunduğunu göstermiştir [19,20,21,22]. Bu grup antibiyotiklere karşı oluşan direnç genellikle transfer edilebilir direnç plazmitleri (R-plazmit) üzerinde bulunmakta ve bu da direncin aynı tür veya farklı tür mikroorganizmalar arasında hızlıca yayı-lımına sebep olmaktadır [23].…”
Section: Discussionunclassified